Functional anatomy : musculoskeletal anatomy, kinesiology, and palpation for manual therapists - Cael, Christy (Philadelphia : Lippincott, Williams & Wilkins, 2010)
'Functional Anatomy' was written to help students of human movement and bodywork understand how anatomical structures work together to create motion. This understanding is essential to students preparing for careers as fitness and sports professionals, who routinely analyze complex movement patterns.
Introduction to the human body -- Osteology and arthrology -- Myology -- Shoulder -- Elbow, forearm, wrist, and hand -- Head, neck, and face -- Trunk -- Pelvis, thigh, and knee -- Leg, ankle, and foot.
This book includes online access, please refer to library staff for the password.
Includes bibliographical references and index.
Keywords: Musculoskeletal System -- anatomy & histology; Movement -- physiology; Musculoskeletal Physiological Phenomena; Palpation